EFEK PENERAPAN LATIHAN FARTLEK TERHADAP PENINGKATAN VO2MAX PADA ATLET PENCAK SILAT - Ali Thamrin; Meirizal Usra; Iyakrus (JURNAL ILMU KEOLAHRAGAAN, 2026)
This study aims to analyze the effect of fartlek training on improving VO₂Max in pencak silat athletes. The method used was a Systematic Literature Review (SLR) with the PRISMA approach to systematically and objectively select relevant articles. Literature searches were conducted through Google Scholar, Lens.org, and ScienceDirect databases with publications ranging from 2020 to 2025. Inclusion criteria included Indonesian-language articles discussing fartlek training and VO₂Max published in national journals. A total of 11 relevant articles were selected for analysis. The results indicate that fartlek training consistently has a significant effect on increasing VO₂Max in pencak silat athletes and other sports. Several studies comparing fartlek with interval and circuit training showed that all methods were effective; however, fartlek training tended to produce more optimal improvements in VO₂Max. Therefore, fartlek training can be considered an effective method for enhancing aerobic endurance in pencak silat athletes. Keywords: Fartlek Training, VO₂Max, Aerobic Endurance, Athletes, Pencak Silat